Transforming the clunky organization : pragmatic leadership skills for breaking inertia - Bacharach, Samuel B. (BLG pragmatic leadership series., 2018)
"This book specifies why organizations fall into patterns of inertia and details the skills leaders need to regain organizational momentum. It includes case illustrations from technology, finance, banking, home entertainment, and retail business sectors. Illustrations are drawn from organizations such as Amazon, Apple, Borders, Merrill Lynch, Nintendo, Starbucks, and Unilever, among many others. The book says that organizational leaders need to continuously explore new opportunities and transfer insights into new products, processes, and directions. They also need to mobilize support for ideas, sustain and drive these ideas forward, and achieve results"--